Análise de algoritmos eficientes para uso em dinâmica molecular ab initio direta - Frederico Teixeira Silva (2014)
A software that integrates classical equations of motion was developed. The program named DRKAI (Dinâmica Runge Kutta ab initio) was first tested in a simple differential equation, which has analytical solution, showing great accuracy in this case. Verified its efficiency, DRKAI was applied in a molecular system, known as molecular dynamics approach. Dynamic results showed good energy conservation and preservation of major feateres of the system. The second part of this paper came when high computational cost was perceived at desired approach. This made imperative the use of efficient algorithms. Many different algorithms are used in current works, making complex the choice of whatshould be implemented. In this thesis a study was made for five integrators. Among these, the symmetric Runge Kutta integrators and Beeman-Verlet were the most efficient, the algorithm of Gauss Radau proved inadequate for long simulations and the algorithm of Runge Kutta Gill proved to be the slowest.